Análisis comparativo del rendimiento térmico de un colector solar de placa plana con la variación de altura en la superficie colectora. - Iza Toapanta, Edison Patricio (2021)
The research project consisted of making a comparison between the thermal performances of a flat plate solar collector with a variation in height in the collected surface, these heights were considered 30 mm and 50 mm, the place of execution of the project was in the province of Cotopaxi, city of Latacunga precisely on the terrace of the old block of the Technical University of Cotopaxi, for the construction of the solar collector mechanical materials were used such as: the structure, covered with 4 mm glass, a polyurethane sheet such as insulation thermal and a collection surface, electronic equipment such as microcontrollers and temperature sensors were implemented for the acquisition and recording of data such as temperature in the glass, temperature in the collection chamber and temperature in the collecting plate, additionally a meteorological station was included with the need to record solar radiation, wind direction and speed, can be contrasted It is clear that for a height variation of 30 mm of the solar collector an average temperature in the glass cover of 20.9 ° C is obtained, an average temperature in the collector plate of 24.30 ° C, an average outlet temperature of 20.88 ° C, the maximum amount of heat reached is 93.88 W and an average efficiency of 64.61%, while with a height of 50 mm a temperature in the glass cover of 19.78 ° is obtained C, an average temperature on the collector plate of 22.73 ° C, an average outlet temperature of 21.35 ° C, the maximum amount of heat achieved is 196.86 W, and an average efficiency of 63.39%.